THE RELATIONSHIPS OF SELF CONTROL AND NEUROTICISM PERSONALITY TENDENCY TO UNHEALTHY CREDIT CARD USAGE OF CAREER WOMEN IN SURABAYA - Sandy, Devi Adilah; Renanita, Theda (Jurnal Entrepreneur dan Entrepreneurship, 2018)
Everyone can experience stress especially career women. Their work problems can cause stress. Career women go shopping to reduce their stress. Then, credit card become their alternative payment method to pay. However, if the use of credit card is not properly managed, it can lead to unhealthy usage of credit card. This research will explore correlation between three variables there are self-control, neuroticism personality tendencies dan unhealthy usage of credit card. Total participants are 73 career women. Multiply correlation analysis shows self-control and neuroticism personality tendencies are related with unhealthy usage of credit card among career women in Surabaya (R=0.447 ρ=0.000); Partial correlation analysis shows (1) There is no relation between self-control and the unhealthy usage of credit card among career women in Surabaya (r=-0.266 ρ=0.024); (2) There is no relation between neuroticism personality tendencies and the unhealthy usage of credit card among career women in Surabaya (r=0.321 ρ=0.006).